Analysis of the usability quality of vocational high school websites using a user satisfaction approach - Rochmat Husaini; Bagus Muhammad Akbar; Ahmad Taufiq Akbar (Jurusan Teknik Informatika, 2022)
Purpose: knowing the extent to which aspects that affect the level of user/visitor satisfaction in using the website.methodology: the method used is usability approach to measure website visitor satisfaction using Structural Equation Model (SEM) theory and SmartPLS v.3.2.9 software.Findings/result: found several variables that influence user satisfaction, and found variables that had no effect, even having a negative dependency value. In addition, it also produces priority recommendations for website improvement to meet user satisfaction.Originality: this study uses the palmer model usability approach [13] and the structural equation model. Which is different from previous research using the webqual method and Importance Performance Analisys [3]